Potential of Black Garlic Nanoparticles as Skin Care - Andiarna, Funsu; Hidayati, Irul; Agustina, Eva (State Islamic University of Sunan Ampel, 2024)
Mask is a beauty product that serves to treat and maintain the skin of the body and face. Black garlic contains antioxidant compounds so that it can counteract free radicals that cause premature aging, wrinkled and dull skin. The purpose of this study was to determine the potential of black garlic nanoparticles as skin care. The aim of this research is to develop a face mask product based on black garlic nanoparticles. The research method is by extracting black garlic by maceration and making nanoparticles of black garlic extract with a silver reducing agent. Black garlic extract nanoparticles were substituted for the manufacture of peel-off masks and tested for their characteristic. The results showed that the black garlic nanoparticle mask had a strong antioxidant activity of 21.168 ppm, the particle size is 59.47 nm and had good characteristics as a peel-off mask based on the viscosity, spreadability, drying test. Black garlic masks with nano-sized particles are able to penetrate the skin's pores more effectively, thus aiding in the repair of damaged skin cells.